USE OF DIGITAL MEDIA AND TECHNOLOGY IN THE LEARNING PROCESS BY TEACHER SDIT BAITUSSALAM - Putra, Lovandri Dwanda; Hedrina, Lusy; Idam, Devi Akita; Arifa, Dian Nur (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Mataram, 2024)
The world of education is currently increasingly developing. In the past, learning in schools usually used manual methods, namely teachers explained lessons in class by explaining directly to students . The aim of this research is to determine the use of digital media and technology at SDIT BAITUSSALAM. The research method used is descriptive qualitative. Media and technology in the world of education today is increasingly developing, one of which is at SDIT BAITUSSALAM. The school also has information technology-based facilities and infrastructure available . The technology at SDIT BAITUSSALAM uses computers. Learning media also plays an important role in the learning process to support smooth teaching and improve student learning outcomes . SDIT BAITUSSALAM utilizes learning media available in schools, for example maps, globes, atlases and photos of the Garuda Pancasila bird for classroom learning. Meanwhile, the technology used is LCD projectors and laptops. How to use it: Teachers usually use Kahoot and Quiziz for classroom learning . An interesting learning atmosphere at SDIT BAITUSSALAM, by using the Student Center Learning learning method teachers can invite students to be more active.